2013
DOI: 10.3389/fnbeh.2013.00120
|View full text |Cite
|
Sign up to set email alerts
|

Supramodal neural processing of abstract information conveyed by speech and gesture

Abstract: Abstractness and modality of interpersonal communication have a considerable impact on comprehension. They are relevant for determining thoughts and constituting internal models of the environment. Whereas concrete object-related information can be represented in mind irrespective of language, abstract concepts require a representation in speech. Consequently, modality-independent processing of abstract information can be expected. Here we investigated the neural correlates of abstractness (abstract vs. concre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 93 publications
4
25
0
1
Order By: Relevance
“…5B, right), outside the region where emblems differ from pantomimes. Weak effects of abstractness/ concreteness are compatible with current results showing comparable activity in the lateral temporal cortex for abstract and concrete words (Bedny et al, 2008;Hernández et al, 2014;, and abstractness/concreteness effects in regions outside this territory (Binder et al, 2009;Straube et al, 2013). In summary, although emblems and pantomimes elicited comparable activity in the largest part of left and right MTG, they differed in two clusters.…”
Section: Pantomimes Versus Emblemssupporting
confidence: 90%
“…5B, right), outside the region where emblems differ from pantomimes. Weak effects of abstractness/ concreteness are compatible with current results showing comparable activity in the lateral temporal cortex for abstract and concrete words (Bedny et al, 2008;Hernández et al, 2014;, and abstractness/concreteness effects in regions outside this territory (Binder et al, 2009;Straube et al, 2013). In summary, although emblems and pantomimes elicited comparable activity in the largest part of left and right MTG, they differed in two clusters.…”
Section: Pantomimes Versus Emblemssupporting
confidence: 90%
“…In terms of phoneme processing, the left middle temporal cortex would be expected to play a major role, as it is an integral part of speech and word processing (Hickok and Poeppel, 2007). In fMRI studies, the peak location for differences between our groups found for the beta band has been frequently associated with activations during listening to speech in various ways (Narain et al, 2003;Oechslin et al, 2010;Straube et al, 2013b;Nagels et al, 2013;Evans et al, 2016, Wolf et al, 2017.…”
Section: Isc Differences Between Dyslexics and Controlsmentioning
confidence: 85%
“…Otros hallazgos provenientes de estudios de neuroimagen funcional describen que, mientras que la integración auditivovisual está más relacionada con la región angular derecha [31], la región angular izquierda parece estar más involucrada en redes de procesamiento abstracto independiente de la modalidad sensorial [32]. De hecho, Fairhall y Caramazza [33] proponían que la región angular izquierda era parte de una red intermodal que intervenía en la representación conceptual de los objetos.…”
Section: Introductionunclassified